Is levonorgestrel intra-uterine system in menorrhagia: effective and acceptable? A retrospective study - Rajan, Niranjana; Nathan, Navina; Vijayakrishnan, Mala; Natarajan, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: This study aimed to evaluate the effectiveness, acceptability, satisfaction and continuation rates of the levonorgestrel intrauterine system (LNG-IUS) in women with heavy menstrual bleeding (HMB) and to assess associated adverse effects. Methods: This retrospective study was conducted in the Department of Obstetrics and Gynaecology, Vijaya Hospital, Chennai. Fifty-five women who underwent LNG-IUS insertion for HMB between January 2023 and January 2025 were identified from outpatient records. Demographic details, co-morbidities, menstrual patterns, ultrasound findings, and histopathology reports were reviewed. Follow-up assessments at 3 and 6 months included evaluation of menstrual blood loss, dysmenorrhea, side effects, and satisfaction scores. Continuation and acceptability rates were documented. Patient satisfaction was measured on a 1-5 scale. Results: The mean age of participants was 42.3 years, and 78% were overweight or obese. A significant reduction in menstrual blood loss was observed, with 90% showing improvement by 6 months. Amenorrhea occurred in 44%, normal bleeding in 26%, and spotting in 20% of women. Dysmenorrhea decreased from 64% at beginning to 4% at 6 months. The continuation rate was 90% and the overall satisfaction score was 74.5%. The LNG-IUS expulsion rate was 10%. The most common adverse effects were spotting (25%) and simple ovarian cysts (20%). Conclusions: LNG-IUS is an effective, acceptable, and minimally invasive therapeutic option for HMB, offering substantial improvement in symptoms, high continuation rates, and favourable tolerability. It serves as a safe and cost-effective alternative to conventional medical and surgical treatments.